Efficacy and toxicity of the combination regimen "docetaxel + cisplatin + leucovorin + 5-fluorouracil" in disseminated gastric cancer - Benjamin K. Hartley, Wattson F. Booth, Alexander M. Sinclair (Academic Journal of Clinicians, 2024)
The aim of our study was to investigate the efficacy and toxicity of the combination regimen of “docetaxel 75 mg/m2, cisplatin 75 mg/m2 on day 2, leucovorin 50 mg intravenously by jet stream, 5-fluorouracil 500 mg/m2 on days 1–3” as first-line chemotherapy for disseminated gastric cancer. The study included 42 patients. Partial regression was observed in 34.1%, disease stabilization in 36.6%, and disease progression in 29.3%. The median progression-free survival was 5.4 months, overall survival was 11.7 months, 1-year survival was 42.8%, 2-year survival was 14.3%, and 3-year survival was 9.5%. In 2 patients, complete resorption of distant metastases was observed during treatment, which allowed them to undergo radical surgery and significantly increase life expectancy - up to 43 months and 53 months. The toxicity of the regimen was moderate. Neutropenia of grade 3–4 was observed in 59.5% of patients and was accompanied by febrile fever only in 1 patient. Non-hematological toxicity of grade 3 was noted in 5 patients (11.9%): in the form of diarrhea – in 7.2%, stomatitis – in 2.4%, asthenia – in 2.4% of patients. This regimen demonstrated comparable efficacy to the DCF regimen in the V-325 study, but a more favorable toxicity profile, allowing chemotherapy to be administered more frequently on an outpatient basis.